Ocorrência e uso de habitat da baleia-de-Bryde (Balaenoptera edeni Anderson, 1878) (Mammalia: Cetacea, Balaenopteridae) na região de ressurgência de Cabo Frio, RJ - Carneiro, Andréa Daniela Venturotti Nunes (2005)
Bryde's whale occurrence has been commonly related to upwelling ecosystems in different areas. But there are deficient data about the biology and behavior of this rorqual restricted to the tropics. The distance sampling method was used between 2000 and 2003, by the Grupo de Estudos de Mamíferos Marinhos da Região dos Lagos for monitoring cetaceans from a shore base, at Arraial do Cabo, southeastern of Brazil. Resulting of 2816h of effort with 203 B. edeni observed. This study provided a clear picture of the seasonal variation of this whale which had the highest frequency during the austral spring-summer compared to others cetaceans at the area. Bryde's whale prefer surface temperatures between 16-18ºC, as showed by the higher index of sightings per unit effort, reflecting the productive phase of Cabo Frio coastal upwelling process. Bryde's whale fed primarily on schooling fish such as sardines and was most abundant during the months of March-April when the schooling fish catches are higher than 20 ton. Data on feeding events were available when interaction with marine birds and small cetaceans was abundant. The seasonality and occurrence of B. edeni appears to show more correlation with the presence of prey of the proper kind and adequate quantities, than with the given range of temperature. Arraial do Cabo showing a coastal upwelling, is a feeding ground of Bryde's whale and can probably be used for also nursing and resting. Further studies are needed to better understand the habitat use pattern of the specie at this upwelling area.